Reinterpretasi Ḥifẓ an-Nasl menurut At-Ṭāhir bin ‘Āsyūr dan Relevansinya terhadap Konsep Ketahanan Keluarga: Reinterpretation of Ḥifẓ an-Nasl according to At-Ṭāhir bin ‘Āsyūr and its Relevance to the Concept of Family Resilience - Alwan Subaki; Khafid, Khafid Abadi (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This article explores the reinterpretation of the concept of ḥifẓ an-nasl by contemporary maqāṣid scholar Muhammad At-Tahir bin ‘Ashur and its relevance to the development of family resilience. Unlike classical scholars who tend to view ḥifẓ an-nasl in a protective sense—mainly through the prohibition of adultery to safeguard lineage—Ibnu ‘Āshūr offers a more proactive and comprehensive approach. He incorporates aspects of education, economy, social well-being, and psychology as integral parts of lineage protection. This study employs a qualitative library research method using the maqāṣid asy-sharī‘ah framework. The findings indicate that the expanded concept of ḥifẓ an-nasl supports the strengthening of five key indicators of family resilience: family unity, physical resilience, economic stability, social cohesion, and psychological well-being. Thus, Ibnu ‘Āshūr’s thought provides a significant contribution to building families that are not only legally valid but also holistically strong and prosperous in the face of modern challenges.